Automatic guiding mechanism for feeding - LIANG RUIWEN (2024)
An automatic guiding mechanism for feeding comprises a guiding assembly. The guide assembly comprises a base and a correction mechanism. The outer contour of the base is in an L shape. The base comprises a base body, a mounting hole and a stepped groove. The correcting mechanism comprises a springback piece, a limiting pin, a rotating pin and a correcting rod. And the springback piece pushes one end of the correction rod to rotate. The base is arranged, and the correction mechanism is movably arranged at one end of the base. And the rotating shaft is rotationally arranged on the rotating pin through the rotating shaft hole. And a guide face is obliquely arranged on the side, back on to the limiting part, of the correcting rod, the plate is guided into the correcting part through the guide face, automatic straightening is completed, and high practicability is achieved. 一种投料自动导正机构，其包括导正组件。所述导正组件包括基座，以及校正机构。所述基座的外轮廓呈L型。所述基座包括基座主体，安装孔，以及阶梯槽。所述校正机构包括回弹件，限位销，转销，以及校正杆。所述回弹件推动所述校正杆的一端转动。通过设置所述基座，以及活动设置在所述基座一端部的校正机构。通